Implementation of Liquidity, Profitability, Solvency and Activity on Stock Prices of Food and Baverages Sub Sector Companies Listed on the Indonesia Stock Exchange (IDX) for the 2017-2021 Period - Sutopo Sutopo (LPPM of NAROTAMA UNIVERSITY, 2022)
Purpose: Determine the effect of liquidity ratios, profitability, solvency and activities of food and beverage sub-sector companies listed on the Indonesia Stock Exchange on stock prices. Design/methodology/approach: The analysis carried out is quantitative analysis using multiple linear regression to answer the problem formulation and determine the effect of predetermined variables. Findings: Profitability, solvency and activity variables partially affect stock prices, liquidity variables partially have no effect on stock prices. Simultaneously, the variables of liquidity, solvency, profitability and activity affect the stock price of banking companies listed on the Indonesia Stock Exchange. Practical implications: Intensify business in the economic field Originality/value: This paper is original Paper type: Research paper